2015 UNFCCC Paris summit : India's dilemma - Shobhane, Gaurav, (SAGE knowledge. Cases., 2016)
In December 2015, 196 countries met in Paris to reach a new global climate change agreement. This case looks at the climate negotiation process from the eyes of India's environment minister, Mr Prakash Javadekar.